The effect of NiAl content on the microstructure and properties of CoCrFeNi–NiAl–Nb pseudo-ternary triple-phase hypoeutectic high-entropy alloys - Zhongheng Diao; Zhenjun Gao; Jiankun Yang; Dongdong Xia; Huijun Kang; Guangwei Zhao; Bo Li; Dong Fang; Xicong Ye (Journal of Materials Research and Technology)
Eutectic high-entropy alloys (EHEAs) have garnered significant attention due to their uniform and fine microstructure, exceptional casting properties, and broad range of industrial applications. A series of triple-phase hypoeutectic high-entropy alloys (HEAs), designated as (CoCrFeNi)93-x(NiAl)xNb7 (where x = 8, 12, 16, 19, 22, 26, 32), were developed in the present experiments. With the exception of the NiAl-8 alloy, all other compositions exhibited FCC, B2, and Laves phases, characterized by topologically densely arranged lattice structures (TCP). The yield strength of the alloy increased from 866.8 ± 20 MPa to 1459.8 ± 16 MPa, while the elongation decreased from 31.29 ± 0.36 % to 16.83 ± 0.16 % as the NiAl content increased. Among the alloys tested, the NiAl-16 alloy exhibited remarkable plasticity, with a yield strength of 961.4 ± 12 MPa, a fracture strength of 2089.4 ± 18 MPa, and a plastic strain of 33.99 ± 0.18 %. These results clearly indicate that this type of alloy has significant potential for engineering applications. Furthermore, based on the coupling of the ductile FCC phase and the brittle B2/Laves phase in the triple-phase hypoeutectic HEAs, the intrinsic mechanism of the high strength and high plasticity of the alloy is analyzed. The phase prediction of the alloy using thermodynamic parameters indicates that the triple phases—FCC phase, Laves phase, and B2 phase—can be stabilized when conditions 6.7 ≤ VEC <7.8, δ > 5 %, and ΔX > 7 % are met.